Peran Teknologi dalam Pendidikan Agama Islam di SMP Muhammadiyah 56 Binjai Timur: Penelitian - Nur Halizah Palem; Muhammad Nasrullah Ramadhana; Candra Wijaya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the role of technology in supporting the learning process of Islamic Religious Education (IRE) at SMP Muhammadiyah 56 Binjai Timur. The research focuses on the definition of technology, its utilization in IRE teaching, the forms of technology used by IRE teachers, as well as the positive impacts and challenges encountered in the process. This study employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that technology plays a significant role in enhancing the effectiveness and engagement of IRE learning. IRE teachers utilize various technologies such as projectors, online learning applications, and audio-visual media to facilitate the teaching and learning process. Although technology offers benefits such as increased student motivation and interactivity, challenges include limited infrastructure, teachers' lack of technological proficiency, and technical disruptions during class. Therefore, continuous training and adequate support are needed to optimize the role of technology in religious education.